Association between adiponectin‐to‐leptin ratio and heart rate variability in new‐onset paroxysmal atrial fibrillation: A retrospective cohort study. Issue 2 (2nd October 2021) - Zhu, Tongjian; Chen, Mingxian; Wang, Meng; Wang, Zhuo; Wang, Songyun; Hu, He; Ma, Kezhong; Jiang, Hong
Abstract: Background: The adiponectin‐to‐leptin (A/L) ratio has been identified as a potential surrogate biomarker for metabolic disorders. However, it remains unknown whether the serum A/L ratio is associated with heart rate variability in paroxysmal atrial fibrillation (AF). Methods: For this retrospective study, we included consecutive patients who underwent 24‐h long‐range electrocardiogram examination in our center for paroxysmal AF. The results of echocardiography, heart rate variability tests, and blood tests were also retrieved. Multivariate line regression analysis was performed to evaluate identify factors independently associated with heart rate variability. Results: Among the 85 included patients with paroxysmal AF, the median A/L ratio was 1.71. Univariate analysis indicated that patients with a low A/L ratio (<1.71, n  = 42) had a lower high‐frequency (HF) power and a higher hs‐CRP level, low‐frequency (LF) power, and LF/HF ratio than those with a high A/L ratio (≥1.71, n  = 43). Multivariate linear regression analysis showed that the serum leptin concentration was independently and positively associated with LF (β = 0.175, p  = .028), while the serum adiponectin concentration was independently and positively associated with HF (β = 0.321, p  = .001). Moreover, the A/L ratio was independently and negatively associated with the LF/HF ratio (β = −0.276, p  = .007). Conclusions: The A/L ratio was independently and negatively associated with the LF/HF ratio in patients with new‐onset paroxysmal AF.